Evaluation Of Pensi (Corbicula Moltkiana) Fishing Activity In Lake Maninjau, West Sumatera Indonesia - Lukman, Lukman -; I., Setyobudiandi; I., Muchsin; S., Hariadi (Advances in Social Sciences Research Journal, 2018)
Pensi (Corbicula moltkiana) is the name a kind of freshwater mussel, which inhabit the Lake Maninjau, West Sumatra Province, Indonesia. Pensi has been utilized and important for the people in the Lake Maninjau region. The pensi fishing activities continuously will impact to their availability in the future. The purpose of this study is to observe the characteristics of pensi fishing activity in Lake Maninjau. The research conducted at the Maninjau Lake area, District of Tanjung Raya, Agam Regency West Sumatera Province from September 2013 to May 2014. The type of data collected is primary data with a focus on the dimensions and fishing pressure. Measurement methods used are interviews, data collection from fishermen and direct observations in the field. The data collected is then analyzed with descriptive methods. Pensi fishing activities as livelihood relatively available in the region Maninjau, especially for people who have no alternative other business fields. Average catches Pensi by fishermen was 51 liters (L) or 42 kg per day, and total production for all fishermen in Lake Maninjau region is 750 607 kg (751 tons) per year.